Development of Cilok Wakwaw Culinary Business to Improve Entrepreneurial Spirit Early On in the Process of Adapting to Challenges and Technological Advances in the Industrial Age 4.0 Among Students - Putri, Inada Karmita; Imel, Amanda Amelia; Utami, Chindio Putri (CV Media Inti Teknologi, 2024)
Business is an activity carried out by individuals or organizations to make a profit which includes the activities of production, buying, and selling of goods or services. The world's technical advancements have now ushered in the fourth industrial revolution. It has the effect of making nearly all human activity—including commercial activity—online or virtually possible. Business conducted online can be called e-business. One of the e-businesses is e-commerce, namely electronic trading that utilizes the Internet network. Cilok is a food product that is generally made from tapioca flour with a round shape like meatballs. with a chewy texture and is much in demand by the public, especially students. In compiling this scientific article the authors used a qualitative observation method. This study used a subjective methodology to collect information or data. This study's method of gathering data involved distributing a needs questionnaire to both the general public and students. This research aimed to meet the needs and desires of consumers satisfactorily and find out how the level of interest in the Cilok Wakwaw Seblak sauce.